MAKING THE CONTENTS OF LETTERS IN THE NOTARIS IN ISLAM'S LEGAL PERSPECTIVE - Tubus Tubus (Jurnal Pembaharuan Hukum, 2017)
This paper aims to examine the making of the contents of wills examined from the point of view of Islamic law, in practice the reality in the lives of many people who have not heed the word basmallah as an incantation in the contents of the will for the followers of Islam. In this study using sociological juridical method, where the primary data obtained directly from field research, while secondary data obtained from the literature. The results obtained that the way of making the contents of the will and the absence of public legal awareness is optimal for the making of the contents of wills in accordance with Islamic law. And there are still weaknesses in the Making and Implementation of the contents of the current will, when the testament is oral, namely: The absence of the sacred intention or the noble intention of the collector must not necessarily occur; unsecured rights of the recipient, in the event of any problems of the future heirs of the pewasiat; there is a difficulty of proof in the absence of witnesses, when the will is brought before the Court. Law renewal in the making of the contents of the will in the presence of a notary in the perspective of Islamic law are: the reconstruction of its value, the Ideal Formation of the Will, the testament is done in writing witnessed by two witnesses and before the Notary. Ideal Construction Format of Testament Creation. The testament is written in the presence of two witnesses or in the form of a Deed or a Notary Deed. At the head of the will or the Deed or Notarial deed is included a sentence “Basmallah”.